Visit Frequency among Patients with Type 2 Diabetes Mellitus: A Multivariable Poisson Regression Analysis using Indonesia’s National Health Insurance Data 2023 - Muhamad Zakki Saefurrohim; Agustin Putri Rahayu; Akmal Izzuddin Tahir; Blego Sedionoto (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a chronic condition requiring multidisciplinary management to prevent serious complications with increasing diabetes-related visits, higher hospitalization rates, and greater mortality risk. This study aimed to identify factors associated with the frequency of T2DM patient visits to Advanced Referral Healthcare (ARH) facilities within Indonesia’s National Health Insurance (BPJS) system, to support evidence-based improvements in care coordination. Methods: A cross-sectional study was conducted using 2023 BPJS sample data in the diabetes subcategory. A total of 1,312 patients met the inclusion criteria based on complete ICD-X (E11) diagnostic codes. Variables examined included age, gender, marital status, BPJS class and type, domicile, primary healthcare ownership and type, ARH type, admission diagnosis, complication status, and hospitalization history. Multivariable Poisson regression analysis was performed in R-Studio to estimate the Incidence Rate Ratio (IRR). Results: Most patients were adult females (64.25%), married (80.64%), lived in districts (80.79%), enrolled in BPJS class 3 (87.96%), and utilized community health centers (77.13%). Patients with complications had significantly higher visit frequencies (IRR = 1.13; 95% CI: 1.03–1.24). After adjustment, gender (p = 0.049; IRR = 0.91; 95% CI: 0.82–1.00) and complication status (p = 0.012; IRR = 1.13; 95% CI: 1.03–1.24) remained significant predictors. Conclusion: Female patients had fewer visits, while those with complications had higher utilization of ARH services. These findings highlight the importance of gender-sensitive and multidisciplinary approaches to strengthen care coordination and optimize the BPJS referral system for T2DM management.